The Oxford companion to classical civilization - Hornblower, Simon; Spawforth, Antony; Eidinow, Esther (OUP Oxford, 2014)
What did the ancient Greeks eat and drink? What role did migration play? Why was emperor Nero popular with the ordinary people but less so with the upper classes? Why (according to ancient authors) was Oedipus ('with swollen foot') so called?